Prevalence Of Hypertension Among Elderly Women in Slums of Surat City - AB Pawar; R K Bansal; Paresh Bharodiya; Shaishav Panchal; HB Patel; PK Padariya; GH Patel (Medsci Publications, 2010)
This screening study conducted among 105 elderly women residing among the slums of Surat city revealed the virtual absence of screening programmes for hypertension in the vulnerable segment as witnessed by detection of new and undiagnosed case of hypertension in over one thirds of those screened. The universal absence of awareness of the need for regular treatment and follow up and absence of informed decision making is indeed distressing.